Potential Benefits of Vessel Slowdowns on Endangered Southern Resident Killer Whales - Joy, Ruth; Tollit, Dominic; Wood, Jason; MacGillivray, Alexander; Li, Zizheng; Trounce, Krista; Robinson, Orla (Frontiers in Marine Science, 2019)
A voluntary commercial vessel Slowdown trial was conducted through 16 nm of shipping lanes overlapping critical habitat of at-risk southern resident killer whales (SRKW) in the Salish Sea. From August 7 to October 6, 2017, the trial requested piloted vessels to slow to 11 knots speed-through-water. Analysis of AIS vessel tracking data showed that 421 of 951 (44%) piloted transits achieved speeds within one knot of the target (i.e., ≤12 knots) and 55% achieved speeds ≤13 knots. Slowdown results were compared to ‘Baseline’ noise of the same region, matched across lunar months. A local hydrophone listening station in Lime Kiln State Park, 2.3 km from the shipping lane, recorded 1.2 dB reductions in median broadband noise (10-100,000 Hz, rms) compared to the Baseline period, despite longer transit durations during the trial. Filtering for commercial vessels within 6 km radius of Lime Kiln listening station (aiming to remove confounding effects of variability in vessel numbers), and excluding small boat noise, high current and wind speed periods, median noise was reduced by 2.5 dB. The reductions were highest in the 1st decade band (-3.1 dB, 10-100 Hz) and lowest in the 4th decade band (-0.3 dB reduction, 10-100 kHz). A regional vessel noise model predicted noise for a range of traffic volume and vessel speed scenarios for a 1133 km2 ‘Slowdown region’ containing the 16 nm of the trial’s shipping lanes. A temporally and spatially-explicit simulation model was used to evaluate the changes in traffic volume and speed on SRKW in their foraging habitat within this Slowdown region. The simulation model tracked the number and magnitude of noise-exposure events that impacted each of 78 SRKW across different traffic volume-speed scenarios. These metrics were simplified to a cumulative effect termed ‘potential lost foraging time’. The model predicted that the voluntary Slowdown trial achieved 22% reduction in ‘potential lost foraging time’ for SRKW, with 40% reductions under 100% 11 knot participation. Slower vessel speeds reduced underwater noise in the Slowdown area despite longer passage times and therefore suggest this is an effective way to benefit SRKW habitat function in the vicinity of shipping lanes.